2008
DOI: 10.1136/jech.2007.063917
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism, life stress and self-reported health among older adults

Abstract: The APOE4 allele and life-stress factors are associated with SRH, especially in women. Physical exercise is good for health, but benefits may be attenuated among APOE4 allele carriers. This is the first evidence associating a genetic factor and an interaction between APOE4 and physical exercise with SRH. We suggest that well studied genetic factors should be included in health research to control potential heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 77 publications
1
14
0
1
Order By: Relevance
“…The APOE genotypes and alleles in our study population were similar to those reported in previous studies from Japan and Taiwan. 25,26 Although the e3/e3 genotype and e3 allele are common in both Asian and Caucasian populations, a significant difference in the proportion of e4 alleles has been noted. 17,[25][26][27][28] The e4 allele was found in only 5.7% of our control subjects and has been reported in 5%-10% in other Asian populations, compared with a prevalence of 15%-18% in Caucasians (Table 5).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The APOE genotypes and alleles in our study population were similar to those reported in previous studies from Japan and Taiwan. 25,26 Although the e3/e3 genotype and e3 allele are common in both Asian and Caucasian populations, a significant difference in the proportion of e4 alleles has been noted. 17,[25][26][27][28] The e4 allele was found in only 5.7% of our control subjects and has been reported in 5%-10% in other Asian populations, compared with a prevalence of 15%-18% in Caucasians (Table 5).…”
Section: Discussionmentioning
confidence: 98%
“…25,26 Although the e3/e3 genotype and e3 allele are common in both Asian and Caucasian populations, a significant difference in the proportion of e4 alleles has been noted. 17,[25][26][27][28] The e4 allele was found in only 5.7% of our control subjects and has been reported in 5%-10% in other Asian populations, compared with a prevalence of 15%-18% in Caucasians (Table 5). 17,[25][26][27][28] Because the APOE e4 allele is strongly associated with extracranial carotid disease, the lower frequency of the e4 allele in Asians may help explain the low prevalence of this disease in this population.…”
Section: Discussionmentioning
confidence: 98%
“…BRN not working on ward and BRN working on ward . Five control variables were recoded into categorical variables to avoid sparse cells and for the ease of interpretation [42]. Ward size was recoded into 4 categories, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses of APOE genotype used the polymerase chain reaction amplification refractory mutation system (PCR-ARMS) and polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) [25]. APOE4 was categorized in terms of whether or not participants carried at least one copy of the E4 allele (yes/no/unknown) [35]. …”
Section: Methodsmentioning
confidence: 99%
“…Exercise was divided into three categories: less than once per week, two to five times per week, and more than six times per week [35]. The other covariates in this study consisted of the individual demographic characteristics of the participants (gender and ethnicity) [37] and whether the individual had depressive symptomatology [38, 39].…”
Section: Methodsmentioning
confidence: 99%